ASR, Volume 24, n° 1, 2020 - Full Issue - system, journal (African Sociological Review, 2021)
Contents Editorial ..................................................1 Éditorial ..................................................2 General Issue Ebola Cisis in West Africa as the Embodiment of the World. Arguing for a Non-conventional Epistemology of Disease Aetiology Jacquineau Azétsop, Ludovic Lado, Armel Setubi Fosso ........................................... 4 L’impact de la Culture sur les Dynamiques Entrepreneuriales : Application au Cas d’une Banque Tunisienne Fakhri Issaoui .....................................................34 The Scramble for the Partition of the Northern Region of Ghana: Conflict and the Quest for the Coterminality of Cultural and Political Boundaries M. H. A. Bolaji, Mohammed Adam Gariba ..........................................75 Insertion Socioprofessionnelle des Jeunes au Bénin: entre Employabilité Publique, Privée ou Personnelle Gilbert Coovi, Coffi Rémy Noumon .........................................105 Analysis of Frames Used by Namibian Newspapers in their Reportage of The San Community Moses Magadza, Eno Akpabio ......................................131 ‘Surviving like a Bird’: Livelihood Coping Strategies in an Informal Settlement of Windhoek, Namibia Tuwilika Endjala, Lucius Botes .........................................151 Quand le Football Burundais devient un Enjeu Identitaire et Politique Mvutsebanka Celestin, Salvator Nahimana ...............................174 Book Review ‘Embedded Practices’: A Review of Political Corruption in Africa: Extraction and Power Preservation Inge Amundsen (Ed.) Cheltenham: Edward Edgar Publishing ISBN 978 1 78897 251 2 (cased); ISBN 978 178897 252 9 (eBook), (2019) pp +201 Olajide Oloyede ..............................190